IBM KELOMPOK USAHA PENGOLAHAN HINTIP TAHU DAN AMPAS TAHU DI DESA CIPEUJEUH WETAN KECAMATAN LEMAH ABANG KABUPATEN CIREBON - Yusuf Sapari; Rifqi Hidayat; Desy Lusiyana (Swadaya: Indonesian Journal of Community Empowerment, 2019)
Various processing of the remaining production that has been developed in line with market demand. Much of the processing of leftover food production has been converted back into useful and economically valuable products. This is the reason for entrepreneurs and craftsmen looking for loopholes to develop and find new innovations for the rest of the processing of products that can be used as food or as products that can be sold in the free market. The results of the site survey in the field prove that tofu waste is widely used as a mixture of sheep and cattle feed. So that the rest of the production of tofu production such as tofu dregs still has not been processed again into economically valuable processed products such as pepes hintip tofu, tofu crackers, tofu nuggets and tofu dregs. This activity is in the form of training on processing tofu waste into snacks, crackers and sambal from tofu waste. Keywords: processed food products, training, tofu waste.